Determinant Compliance With People's Tax Obligations - Yulianti, Yulianti; Widowati, Lisa Sari; Santoso, Aprih (Jurnal Akuntansi dan Pajak, 2020)
Study aims to determine the effect of tax knowledge, awareness, and knowledge of tax amnesty on individual taxpayer compliance. Research at KPP Pratama East Semarang and KPP Pratama Semarang Candisari. Study uses the Slovin formula to determine the number of samples by purposive sampling method. The analysis technique used is multiple linear regression. The results showed that knowledge of taxation, awareness, and knowledge of tax amnesty had a positive effect on individual taxpayer compliance. Knowledge of taxation, awareness, and knowledge of tax amnesty affect individual taxpayer compliance by 55.7%, while the remaining 44.3% is influenced by other variables.